2′‐Hydroxy Protection of Ribonucleosides as 2‐Cyano‐2, 2‐Dimethylethanimine‐N‐Oxymethyl Ethers in Solid‐Phase Synthesis of RNA Sequences. Issue 1 (16th February 2018) - Cieślak, Jacek; Ausín, Cristina; Grajkowski, Andrzej; Beaucage, Serge L.
Abstract: The reaction of 2′‐ O ‐aminooxymethylribonucleosides with 2‐cyano‐2‐methyl propanal leads to the formation of stable and yet reversible 2′‐ O ‐(2‐cyano‐2, 2‐dimethylethanimine‐ N ‐oxymethyl)ribonucleosides in post‐purification yields of 54% to 82%. Phenoxyacetylation of the exocyclic amino functions of these ribonucleosides proceeds in yields of 74% to 89%, and subsequent 5′‐ O ‐dimethoxytritylation and 3′‐ O ‐phosphitylation of the corresponding N ‐phenoxyacetylated ribonucleosides provide the fully protected ribonucleoside phosphoramidite monomers in isolated yields of 69% to 88%. These ribonucleoside phosphoramidites are employed in solid‐phase synthesis of three chimeric RNA sequences, each differing in purine/pyrimidine content. The stepwise coupling efficiency of the ribonucleoside phosphoramidites (as 0.15 M solutions in acetonitrile) averages 99% over a coupling time of 180 s when 5‐benzylthio‐1 H ‐tetrazole is used as an activator. Upon completion of RNA chain assembly, removal of the nucleobase‐ and phosphate‐protecting groups and release of sequences from the solid support are carried out under standard basic conditions. Finally, the 2′‐ O ‐(2‐cyano‐2, 2‐dimethylethanimine‐ N ‐oxymethyl) protective groups are cleaved from the RNA sequences by treatment with 0.5 M tetra‐ n ‐butylammonium fluoride in dry DMSO for 24 to 48 hr at 55°C without releasing RNA‐alkylating side‐products. Characterization of the fully deprotected RNA sequences by PAGE, enzymatic hydrolysis, and MALDI‐TOF mass spectrometry confirms the identity and high quality of these sequences. Curr. Protoc. Nucleic Acid Chem . 54:3.22.1‐3.22.28. © 2013 by John Wiley & Sons, Inc.